2022
DOI: 10.1126/sciadv.abq1081
|View full text |Cite
|
Sign up to set email alerts
|

Astrocytic dysfunction induced by ABCA1 deficiency causes optic neuropathy

Abstract: Astrocyte abnormalities have received great attention for their association with various diseases in the brain but not so much in the eye. Recent independent genome-wide association studies of glaucoma, optic neuropathy characterized by retinal ganglion cell (RGC) degeneration, and vision loss found that single-nucleotide polymorphisms near the ABCA1 locus were common risk factors. Here, we show that Abca1 loss in retinal astrocytes causes glaucoma-like optic neuropathy in aged mice. AB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 73 publications
0
11
0
Order By: Relevance
“…C57BL/6 mice are nearly genetically identical with only ∼15,000 SNPs and insertion–deletion mutations (indels) ( Doran et al, 2016 ), providing evidence that SNP-based demuxers are unable to separate biological replicates from highly inbred mice. We also attempted SNP-based demultiplexing of in silico–pooled data from DBA/1J mice ( Shinozaki et al, 2022 ) which have ∼5 × 10 6 total SNPs and indels ( Doran et al, 2016 ). Again, 99.7% of cells were unable to be assigned via souporcell (data not shown), suggesting that SNP-based demultiplexing is incompatible with highly inbred animals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…C57BL/6 mice are nearly genetically identical with only ∼15,000 SNPs and insertion–deletion mutations (indels) ( Doran et al, 2016 ), providing evidence that SNP-based demuxers are unable to separate biological replicates from highly inbred mice. We also attempted SNP-based demultiplexing of in silico–pooled data from DBA/1J mice ( Shinozaki et al, 2022 ) which have ∼5 × 10 6 total SNPs and indels ( Doran et al, 2016 ). Again, 99.7% of cells were unable to be assigned via souporcell (data not shown), suggesting that SNP-based demultiplexing is incompatible with highly inbred animals.…”
Section: Resultsmentioning
confidence: 99%
“…C57BL/6 data were downloaded from SRR15502048 , SRR15502052 , and SRR15502056 ( Crowl et al, 2022 ). For DBA data ( Shinozaki et al, 2022 ) possorted.bam files were downloaded from SRA. wget https://sra-pub-src-1.s3.amazonaws.com/SRR20079758/WT3_possorted_genome_bam.bam.1 wget https://sra-pub-src-1.s3.amazonaws.com/SRR20079759/WT2_possorted_genome_bam.bam.1 wget https://sra-pub-src-2.s3.amazonaws.com/SRR20079760/WT1_possorted_genome_bam.bam.1 .…”
Section: Methodsmentioning
confidence: 99%
“…This vicious cycle between tau hyperphosphorylation and oxidative stress [113], as well as tau aggregate formation, can induce glial inflammation (astrogliosis) and neuropathology in Alzheimer's disease-related mouse models via innate immune sensors (receptors) such as Tool-like receptors (TLRs) [119]. In fact, tau-containing astrocytes have been discovered in numerous tauopathies, including glaucoma [120,121].…”
Section: Oxidative Damage Is a Common Feature In Both Glaucoma And Ta...mentioning
confidence: 99%
“…In another example, inspired by the relationship between aging and glaucoma in clinical settings, Lu et al designed retinal tissue reprogramming through the induction of ectopic expression of the four Yamanaka transcription factors and showed reverse age-related vision loss and eye damage in an aging mouse model with glaucoma (6). These and other related studies demonstrated the successful implication of reverse translation in glaucoma research (7)(8)(9).…”
Section: Introduction 1reverse Translation In Glaucoma Studiesmentioning
confidence: 99%